Frequency of Prostatic Adenocarcinoma in Men with Clinical suspicion of malignancy using TURP/Trans rectal Prostate Needle Biopsies with emphasis on Gleason score/grade - Naima Gul, Fazeelat Iftikhar, Ammara Ijaz, Naghmana Iftikhar, Hira Anum, Hira Anum, Naima Gul, Fazeelat Iftikhar, Ammara Ijaz, Naghmana Iftikhar, Hira Anum, Hira Anum (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Prostatic pathologies have always stayed the reason of concern in men above 50 years of age; the most dreaded of these is prostatic carcinoma. Progress in medical field has led to development of new investigative and treatment modalities in this domain. The current study is aimed at determining the frequency of prostatic adenocarcinoma in men with clinical suspicion of malignancy using transurethral resection of the prostate (TURP)/trans rectal prostate needle biopsy, using modified Gleason scoring system. Methods: A descriptive cross-sectional study of histopathological findings of 178 specimens was conducted for men undergoing TURP/trans rectal needle biopsy during a period of 3 years from January 2014 to January 2017 at Benazir Bhutto Hospital, Rawalpindi, Pakistan. Results: The histopathological findings of TURP/trans rectal prostatic needle biopsies of 43(24.2%) specimens confirmed prostatic adenocarcinoma. Of the rest 133 (74.7%) were diagnosed as benign prostatic hyperplasia, and 2 (1.1%) squamous metaplasia. Mean age of all patients was 65.8±9.02 years. The tagging of the 43 cases of prostatic adenocarcinoma on the basis of Gleason score disclosed that 17 cases (39.5%) had Gleason grade pattern IV followed by 13 cases of Gleason grade pattern III (30.2%) and 8 cases of Gleason grade pattern II (18.6%). Conclusion: Prostatic adenocarcinoma was noted in 24.2% of our patients with clinical suspicion of prostatic malignancy. Grade IV and II Gleason grade was noted in majority of these patients.